Pengaruh Overinvestment Modal Kerja, Underinvestment Modal Kerja Terhadap Kinerja Perusahaan - Santoso Adi Susatyo; Yanuar Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The main objective of this research is to dissect how different levels of Working Capital investment affect business results. The two separate studies that make up this research are the research of Overinvestment in Working Capital and the study of Underinvestment in Working Capital. Return On Assets (ROA), a measure that represents a measure based on how well a company performs. 11 companies involved in car production were part of this study. With 66 data points making up the sample. This research found that from 2018 to 2023, the financial performance of automotive manufacturing sector companies listed on the IDX was not affected by the amount of Working Capital invested, whether too much or too little. Company performance decreases when there is a lack of investment in Working Capital. In summary, the findings of this study add credence to the idea that controlling Overinvestment and Underinvestment of Working Capital is critical to a company's success and draw attention to risks that management must be aware of. To maximize profits, managers can utilize this study to optimize Working Capital for business prospects.